1991
DOI: 10.1159/000470433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Decrease in Aortic Compliance on the Isovolumic Relaxation Period of the Left Ventricle in Man

Abstract: A decrease in aortic compliance can modify the loading sequence to the left ventricular ejection in the elderly. To determine whether a decreased aortic compliance influences the left ventricular relaxation in man, 83 healthy volunteers, aged 34-87 years, were studied. The left ventricular relaxation was characterized by the isovolumic relaxation period (IRP) of the left ventricle. The aortic compliance was characterized by the aortic pulse wave velocity (AoPWV). The loading sequence to left ventricular ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…There was a positive univariate association between these two variables, with an increase in E/A ratio evident with increasing arterial compliance. Pulse wave velocity, which is a measure of arterial compliance, has previously been shown to be related to the isovolumic relaxation period of the left ventricle 22 . However, E/A was also related to a number of other variables, which were themselves related to SAC.…”
Section: Discussionmentioning
confidence: 95%
“…There was a positive univariate association between these two variables, with an increase in E/A ratio evident with increasing arterial compliance. Pulse wave velocity, which is a measure of arterial compliance, has previously been shown to be related to the isovolumic relaxation period of the left ventricle 22 . However, E/A was also related to a number of other variables, which were themselves related to SAC.…”
Section: Discussionmentioning
confidence: 95%
“…Other equivalents, such as aortic input impedance and effective arterial elastance, reflect the pulsatile components of left ventricular afterload [41][42][43]. Aortic stiffness can be assessed most easily by measurement of pulse wave velocity (Cw), with a high Cw indicating increased stiffness and vice versa [14,18,[30][31][32][33][34][35][36][44][45][46][47][48][49][50]. The pulse wave velocity mirrors the average stiffness of the aortic pathway and can provide more information than techniques measuring the aortic diameter at only one defined site [51].…”
Section: Assessment Of Aortic Elastic Propertiesmentioning
confidence: 99%
“…Cardiovasc Drugs Ther 1996;10: [49][50][51][52][53][54][55][56][57] Key Words. aortic stiffness, arterial distensibility, pulse wave velocity, Windkessel function, cilazapril, hydrochlorothiazide Increased stiffness of the aorta and the large elastic arteries leads to a reduction of their buffering windkessel function and is a major component in the pathophysiology of systolic hypertension [1][2][3][4].…”
mentioning
confidence: 99%
“…26 Moreover, LV relaxation could be further altered by the loss of aortic compliance evidenced in MFS. 36 Ochi et al 37 have shown that the length of the relaxation period is inversely related to aortic compliance. Reduced left ventricle compliance can be easily attributed to alterations of connective tissue leading to an increased stiffness of the left ventricle as well as of the aortic wall.…”
Section: Discussionmentioning
confidence: 99%